Evaluasi dan Optimasi Ukuran Komponen Penyusun Pembangkit Listrik Tenaga Hibrid Sistem Inovasi Daerah Pantai Baru - , AJI N. PAKHA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rising demand for electricity and fossil fuel will deplete fossil fuel reservoir, therefore proper solution by the government to overcome the problem through the utilization of new and renewable energy is required. The Hybrid Power System Regional Innovation in Pantai Baru is an implementation of new and renewable energy hybrid power system which is partnership among the government, the private sector, the universities, and the surrounding local community. This research focus to do evaluation and optimization for selling electricity PLTH Pantai Baru using Benefit Cost Ratio analysis and HOMER software. The variables of evaluation and optimization PLTH Pantai Baru are maximum capacity shortage, hourly loads, solar power output, cost of energy and net present cost. The results of the study show that section with load 346 kWh/d, would produced 20 % of power need by the load, with the PV produced 20491 kWh/year and wind turbine produced 8184 kWh/year . The optimization result with a low net present cost and low cost of energy is the configuration PLTH 3 with PV power 136610 kWh/year and is also visible to sell electricty.